Strategy and organizational culture – Conceptualizing the interplay of key concepts in communication - Luisa Winkler; Ansgar Zerfass (Globe, 2016)
Organizational culture and strategy have had a long and varied history in communication research. Different definitions go hand in hand at several levels to analyze their nature and impact. The cultural roots of organizations and the need for flexible strategic communication raise the question: What are the similarities between organizational culture and strategies and do both concepts influence each another?